Factors that Increase the Risk of Inflammatory Bowel Disease (World Journal of Current Medical and Pharmaceutical Research, 2024)
Inflammatory bowel disease (IBD) is a chronic disorder of the gastrointestinal tract. It comprises Crohn’s disease (CD) and ulcerative colitis (UC) The disorder begins in young adulthood. It is characterised by remission and relapse. IBD significantly affects a person’s life more so, their productivity and ability to perform activities of daily living. Although IBD is prevalent in Western countries, the recent epidemiology data shows a rising global prevalence and incidence. Addressing IBD is important. Although it is not significantly associated with high morbidity rates, it is a significant burden to healthcare. Identifying the risk factors of IBD can help in improving preventative measures. Since IBD does not have a known cure, controlling for these factors can minimize the impact of the disease. Some of the risk factors that increase the risk of IBD are genetics, environmental factors such as smoking, diet, lifestyle changes, medications, and intestinal microbiome. Identifying the factors that contribute to the risk of developing IBD can help in creating effective measures that can prevent the pathogenesis of the disease.